Investigation into current industrial practices relating to product lifecycle management in a multi-national manufacturing company. Issue 5 (2nd September 2016) - Essop, Ismael A.; Evans, Richard D.; Wan, Shan; Giddaluru, Muni P.; Gao, James X.; Baudry, David; Mahdikhah, Sara; Messaadia, Mourad
ABSTRACT: Product Lifecycle Management (PLM) systems have gained growing acceptance for managing all information relating to products throughout their full lifecycle, from idea conceptualisation through operations to servicing and disposal. This paper, through an in-depth exploratory study into a leading power generation manufacturing organization, presents current PLM issues experienced by manufacturing companies, exploring three separate topics: 1) PLM, 2) Knowledge Management and Lessons Learnt and 3) Product Servicing and Maintenance. Following a review of published literature, results of the investigation are presented, analysing the responses of 17 employees interviewed. With respect to Product Development, it was found that information traceability is time consuming and change management requests take too long to complete. Results relating to knowledge management indicate that the Company operates a 'who you know' culture, but do aim to capture lessons learned on the manufacturing shop floor and assembly lines. Therefore, a prototype design is proposed to integrate the capturing of lessons learnt within the existing PLM system. GRAPHICAL ABSTRACT: